Duchowość misyjna jako istotny element osobowości współczesnego misjonarza - Balwierz, Marian (Śląskie Studia Historyczno-Teologiczne, 1982)
From the very beginning of Christianity, the Church have to fight for some good missionaries, especially in the every stage of her history called a „time of mission”. This general observation is also true today. Even is more, the modern context of mission shows that a proper realization of Church’s evangelizing task depends first of all on person of an evangelizer himself today. It depends on the methods of evangelization only with connection with the personality of missionaries. It is also a matter of fact that the missionary Church likes to employ evangelizers from Poland these days. This very good opinion about Polish missionaries comes from another fact. Everyone of them realizes in the missionary circumstances a fashion of fidelity to the mission received from the Resurrected Lord proper for the Church in Poland. According to Pope John Paul II, it is the fashion of the evangelizing testimony and the social services. Both categories, namely the evangelizing testimony and the social service belong to the realm of spiritual personality of missionary. This spiritual personality of evangelizers is a matter of great moment for the evangelization of people among their all another personal values. Actual replacement of an expression „missionary activity” by a term „missionary evangelization” emphasizes also on those connections between the spirituality and the mission of modern missionaries. The most important of them is the care for objectivism of evangelization. Each missionary has to deliver Jesus Christ to the evangelized people in his missionary work. It is obvious that he has to have Him spiritually first or he will be uncapable to do this evangelizing job because he will not possess the essence of that, what has to be delivered in the process of evangelization. This personal possession of Jesus Christ occures and grows through the sacramental life of an evangelizer. Missionary's spirituality standing first of all on those sacramental life enables him also to be a master in the Truth during his work for awakening and intensification of people’s faith. There are two consequences of those facts. First, it is now impossible to define the missionary without some reference to the cathegory of his spiritual life. Second nowadays the Teaching Church pays more and more her attention to this correlation between the spiritual personality of missionary and his mission. A wise synthesis of this particular teaching of the Church can be found in the newest papal document treating on those matters, namely in the apostolic adhortation Evangelii nuntiandi of Pope Paul VI. Papal teaching about the spirituality of missionaries is grounded on a very important rule. The evangelizing mission of the Church is her service to the world in the prophetical order. It is not principally the service to the world in the sociological or psychological orders. Therefore, the first and the most important condition for a good evangelizing is a missionary’s total submission to the Holy Spirit. This Christ-centrical obedience to the Holy Ghost is realized by an evangelizer during his exeptional service as well to the Gospel as to the Church. This missionary’s spirituality of servant reveals itself by an evangelizer’s attitude of witness to Jesus Christ and His Salvation in the more personal dimension. A ground for this attitude of witness is a holiness of evangelizer’s life. The modern missionary develops his holiness of life when he mantains his own sacramental life, his own practice of virtue of prayer and his own spirit of a personal sacrifice. There is no better conclusion for this theological reflexion than a replica of papal words appealing for a personal increase of our own missionary spirituality helping for our own realization of common duty of evangelization.